Staging and Undoing Apartheid’s Spatial Injustice: Heterotopias in Athol Fugard’s The Island - Qi, Yaping (Research in African literatures, 2025)
Spatial injustice persists in the post-apartheid decades in South Africa. Despite a lapse of fifty years after its premiere, Athol Fugard’s The Island still has contemporary resonance for its staging of the spatial injustice that South Africans encountered in the 1960s and 1970s. This article offers an alternative to the dominant thematic reading of the play, arguing that Robben Island and the prison are heterotopias of colony and deviance that work as instruments of normalization to reinforce existing racial segregation and that the improvised stage acts as a heterotopia of illusion to empower the actors to temporarily step out of their cast roles and momentarily see their own subjectivities as discursive constructs. A spatial study of The Island reveals how individuals are spatially defined in the (post)apartheid era and how the double logic of heterotopia, an interplay between normative disciplining and liberating transgression, operates in the play.